Limiting behavior of the solutions to linear second-order parabolic equations - Skrypnik, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Properties of solutions of parabolic equations in smooth cylindrical domains are studied. Conditions for existence of boundary non-tangents and L_2-limits as t → 0 are found.